Effect of pH on Phase, Morphology and Photocatalytic Properties of BiOBr Synthesized by Hydrothermal Method - Prakasit Intaphong (2019)
© 2019, Springer Science+Business Media, LLC, part of Springer Nature. Effect of pH on crystalline structure, morphology and visible-light-driven photocatalysis of BiOBr samples hydrothermally synthesized in solutions with the pH of 2–10 was investigated. The as-synthesized BiOBr samples investigated by X-ray diffraction, Raman spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy, transmission electron microscopy and X-ray photoelectron spectroscopy. In this research, the as-synthesized samples are pure tetragonal BiOBr phase at the pH of 2–10, and were composed of microplates, nanoplates and hierarchical micro-flowers controlled by the solution pH. The as-synthesized sample at the pH 8 was revealed the presence of Bi 4f, O 1s and Br 3d. Visible-light-driven photocatalytic properties of the BiOBr photocatalyst with different morphologies were investigated through the photodegradation of rhodamine B (RhB). The BiOBr hierarchical micro-flowers synthesized in the solution with the pH 8 show the best photocatalytic activity for wastewater treatment and the ·O2− radicals were attributed to be the primary active species for photodegradation of RhB under visible light irradiation.